Concord leasing (Asia) Pte Ltd. - Ng, Thiam Siong. (2009)
The report gives a description of the business attachment program conducted at Concord Leasing (Asia) pte Ltd. It looks at the background, structure 'and business scope of the organization. The section on projects completed will cover the things learnt during the period of attachment. There will also be a brief summary of the business attachment program. I hope this report will be useful for your future reference in choosing organizations for the business attachment program.